2010
DOI: 10.1074/jbc.m110.128561
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Orientation and Catalytic Specificity in the Action of Xanthine Oxidase

Abstract: Xanthine oxidase is a molybdenum-containing enzyme catalyzing the hydroxylation of a sp 2 -hybridized carbon in a broad range of aromatic heterocycles and aldehydes. Crystal structures of the bovine enzyme in complex with the physiological substrate hypoxanthine at 1.8 Å resolution and the chemotherapeutic agent 6-mercaptopurine at 2.6 Å resolution have been determined, showing in each case two alternate orientations of substrate in the two active sites of the crystallographic asymmetric unit. One orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(147 citation statements)
references
References 33 publications
9
134
1
1
Order By: Relevance
“…6, Table 2). It was suggested from the XDH crystal structure that Glu-802 and Arg-880 are essential for the correct positioning/orienting and/or activation of the substrate through the establishment of hydrogen bonds and electrostatic interactions (36), as found in all structures of XOR complexed to inhibitors or substrates (29,(37)(38)(39)(40). Glu-802 in bXDH is replaced by a valine in all AOX1 orthologs and by an alanine (Ala-807) in mAOX3.…”
Section: Crystal Sample Maox3mentioning
confidence: 99%
“…6, Table 2). It was suggested from the XDH crystal structure that Glu-802 and Arg-880 are essential for the correct positioning/orienting and/or activation of the substrate through the establishment of hydrogen bonds and electrostatic interactions (36), as found in all structures of XOR complexed to inhibitors or substrates (29,(37)(38)(39)(40). Glu-802 in bXDH is replaced by a valine in all AOX1 orthologs and by an alanine (Ala-807) in mAOX3.…”
Section: Crystal Sample Maox3mentioning
confidence: 99%
“…The results are shown in Fig. 2 crystallography study has shown that both 6MP and hypoxanthine bind in two orientations that could lead to either oxidation on the five-membered or six-membered ring of either substrate (Cao et al, 2010). While 6MP metabolism was not explored, this study concluded that xanthine (oxidation on the six-membered ring) was the major intermediate of hypoxanthine oxidation and that oxidation on the five-membered ring was not observed.…”
Section: Resultsmentioning
confidence: 77%
“…In contrast, rabbit myocardial endothelial cells lack XO, so the degradation of purine nucleosides, adenosine and inosine, stops at Hx (18). Cao et al (5) observed that at low pH, a small amount of the closely related 6,8-dihydroxypurine formed as an intermediate in the reaction and that it also degraded to Ua; at pH 8.5, almost none formed, so in our analysis this potentially complicating reaction is not considered.…”
mentioning
confidence: 81%
“…They found that in the presence of varied steady-state concentrations of Ua, the half-maximal inhibitory effect was obtained with 178 M Ua and thus used that as K i in Eqs. [5][6][7]. That being the case, the question is how to explain that models 1 and 2, without and with Ua inhibition, fit the data equally well.…”
Section: Which Is the Right Model?mentioning
confidence: 98%